Somewhat saved: a captive breeding programme for two endemic Christmas Island lizard species, now extinct in the wild. Issue 1 (30th November 2016) - Andrew, Paul; Cogger, Hal; Driscoll, Don; Flakus, Samantha; Harlow, Peter; Maple, Dion; Misso, Mike; Pink, Caitlin; Retallick, Kent; Rose, Karrie; Tiernan, Brendan; West, Judy; et al.
Abstract: As with many islands, Christmas Island in the Indian Ocean has suffered severe biodiversity loss. Its terrestrial lizard fauna comprised five native species, of which four were endemic. These were abundant until at least the late 1970s, but four species declined rapidly thereafter and were last reported in the wild between 2009 and 2013. In response to the decline, a captive breeding programme was established in August 2009. This attempt came too late for the Christmas Island forest skink Emoia nativitatis, whose last known individual died in captivity in 2014, and for the non-endemic coastal skink Emoia atrocostata . However, two captive populations are now established for Lister's gecko Lepidodactylus listeri and the blue-tailed skink Cryptoblepharus egeriae . The conservation future for these two species is challenging: reintroduction will not be possible until the main threats are identified and controlled.